Purification and DNA Synthesis in Cell-Free Extracts: Properties of DNA Polymerase II - Kornberg, Thomas (1971)
The major DNA-synthesizing enzyme present in Pol A(1)(-)Escherichia coli (DNA polymerase II) has been purified to homogeneity as judged by polyacrylamide gel electrophoresis. The enzyme requires all four deoxynucleoside triphosphates, Mg(++), NH(4)(+), and native DNA for maximal activity. The enzyme activity is sensitive to sulfhydryl reagents and is insensitive to anti-DNA polymerase I antiserum. A second DNA-synthesizing enzyme, present in low amounts, has been identified in Pol A(1)(-) extracts. The relationship of this enzyme to DNA polymerases I and II is discussed.